2020
DOI: 10.2478/msr-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Basset History Force for the Description of Magnetically Driven Motion of Magnetic Particles in Air

Abstract: Lungs are used as an attractive possibility for administration of different therapeutic substances for a long time. An innovative method of such administration widely studied nowadays is the application of aerosolized magnetic particles as the carriers to the lungs in the external non-homogeneous magnetic field. For these reasons we have studied dynamics of such a system on a level of particle trajectory in air in the presence of magnetic force as a driving force exerted on micrometric magnetic particle. On tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Because of the difficulties associated with calculating the integral term, Basset hereditary force is often ignored. However, in a number of studies, it is shown that Basset hereditary force could influence the bubble dynamics. An integral/quadrature scheme has been developed for the numerical estimation of the Basset hereditary force …”
Section: Introductionmentioning
confidence: 99%
“…Because of the difficulties associated with calculating the integral term, Basset hereditary force is often ignored. However, in a number of studies, it is shown that Basset hereditary force could influence the bubble dynamics. An integral/quadrature scheme has been developed for the numerical estimation of the Basset hereditary force …”
Section: Introductionmentioning
confidence: 99%
“…We consider not only a simple system of ordinary differential equations (ODEs) but also stochastic integro-differential equations (SIDEs), which do not possess a simple analytic or numerical solution. Recently, we showed in [5,47,48] how to approach a similar system of integro-differential equations (IDEs) containing a non-local Basset acceleration history term numerically, with a variable timestep order of one, quadrature scheme. However, the current situation is more complex because the stochastic term brings the additional difficulty of solving the current system of SIDEs with a similar method.…”
Section: Introductionmentioning
confidence: 99%